(untitled) (Update Dental College Journal, 2026)
Background: The timing of dental implant placement, whether immediate or delayed following tooth extraction, significantly impacts clinical outcomes, esthetic results, and patient satisfaction. A comprehensive understanding of both protocols is essential for optimizing treatment planning and success rates. Objectives: This review aims to compare immediate and delayed implant placement in terms of clinical outcomes, survival rates, and patient satisfaction. Additionally, it discusses indications, contraindications, and critical factors influencing the choice between these approaches. Methods: Relevant studies, systematic reviews, and clinical trials from peer-reviewed journals were analyzed to assess the outcomes associated with both immediate and delayed implant placements. Key parameters evaluated included implant survival, esthetic results, patient-reported satisfaction, and complications. Results: Both immediate and delayed implant placement protocols demonstrate high survival rates, often exceeding 95%. Immediate placement offers advantages such as reduced treatment time, preservation of alveolar bone, and enhanced patient satisfaction. However, it carries risks related to primary stability and esthetic outcomes, particularly in cases with compromised extraction sites. Delayed placement allows for better healing and bone regeneration but may require additional surgical interventions due to alveolar ridge resorption. Conclusion: Immediate and delayed implant placements are both viable and predictable when appropriate patient selection and surgical techniques are applied. Immediate placement is preferable when conditions are ideal, while delayed placement remains the standard when managing infection, bone defects, or poor soft tissue quality. Careful evaluation of patient-specific factors is critical to achieving optimal clinical and esthetic outcomes. Update Dent. Coll. j: 2025; 15(2): 39-44